The Growing Medical Need for Tracheal Replacement: Reconstructive Strategies Should Overcome Their Limits - Adamo, Davide; Galaverni, Giulia; Genna, Vincenzo Giuseppe; Lococo, Filippo; Pellegrini, Graziella (Frontiers in Bioengineering and Biotechnology, 2022)
Breathing, being predominantly an automatic action, is often taken for granted. However, respiratory diseases affect millions of people globally, emerging as one of the major causes of disability and death overall. Among the respiratory dysfunctions, tracheal alterations have always represented a primary challenge for clinicians, biologists, and engineers. Indeed, in the case of wide structural alterations involving more than 50% of the tracheal length in adults or 30% in children, the available medical treatments are ineffective or inapplicable. So far, a plethora of reconstructive approaches have been proposed and clinically applied to face this growing, unmet medical need. Unfortunately, none of them has become a well-established and routinely applied clinical procedure to date. This review summarizes the main clinical reconstructive attempts and classifies them as non-tissue engineering and tissue engineering strategies. The analysis of the achievements and the main difficulties that still hinder this field, together with the evaluation of the forefront preclinical experiences in tracheal repair/replacement, is functional to promote a safer and more effective clinical translation in the near future.